Rifaximin Alfa and Liver Diseases: More Than a Treatment for Encephalopathy, a Disease Modifier - Torre A; Córdova-Gallardo J; Frati Munari AC (Dove Medical Press, 2023)
Aldo Torre,1,2 Jacqueline Córdova-Gallardo,3 Alberto C Frati Munari4 1Guest Research, Metabolic Unit Department, Instituto Nacional de Ciencias Médicas Y Nutrición "Salvador Zubirán", México City, Mexico; 2Guest Research, Liver Unit Department, Hospital General de México, México City, Mexico; 3Hepatology department, Hospital General Dr. Manuel GEA González, Mexico City, Mexico; 4Internal Medicine Department; Hospital Médica Sur, Mexico City, MexicoCorrespondence: Aldo Torre, Guest Research, Metabolic Unit Department, Instituto Nacional de Ciencias Médicas Y Nutrición "Salvador Zubirán", México City, Mexico, Email detoal@yahoo.comAbstract: RFX, a rifamycin-based antibacterial agent obtained by the culture of the actinomycete Streptomyces mediterranei, has a broad antibacterial spectrum covering gram- positive, gram-negative, aerobic, and anaerobic bacteria. RFX is an antibiotic that elicits its effect by inhibiting bacterial RNA synthesis. When administered orally, its intestinal absorption is extremely low (< 0.4%), restricting antibacterial activity mainly in the intestinal tract, with few systemic side effects. RFX has been recommended by the American Association for the Study of Liver Diseases and the European Association for the Study of the Liver guidelines for the treatment of HE. RFX may contribute to restore hepatic function and to decrease the development of liver fibrosis. Its efficacy has been shown in patients with previous hepatic encephalopathy and several complications, such as infections, including spontaneous bacterial peritonitis, ascites and oesophageal variceal bleeding. Thus, RFX has an outstanding role in the therapeutic arsenal in hepatic cirrhosis, under the concept of disease modifier.Keywords: rifaximin, liver disease, modifier, hepatic cirrhosis therapy